O Gênio Ródio de Alexander Von Humboldt / The Alexander Von Humboldt’s Rhodium Genius - Roberison Wittgenstein Dias Silveira (Sociedade & Natureza)
In this paper we will analyze the Humboldt’s Rhodium Genius and philosophical implications of its publication. The essential task is to outline the interpretive possibilities and philosophical-systematic character of the work, pondering the interpretive possibilities of this publication in the course of the Humboldt life. Considering the important aesthetic debate of the period and as reason and sensibility have become mutually dependent on romantic idealist solution, the paper seeks to clarify the representative dimension of Rhodium Genius and its importance in the transformation that occurred between the years 1795 (date of first publication) and 1849 (date of the last edition of Frames of Nature). At the end, entering the scientific, aesthetic and philosophical debate, we will have the opportunity to see how Humboldt’ Rhodium Genius allowed the first incorporating scientific of the landscape concept as dual objective/subjective in the construction to an aesthetic-philosophical science of the Cosmos.